DESAIN DATA AKUISISI BOMB KALORI METER BAHAN BAKAR CAIR - Junaidi Junaidi; Fadly Ahmad Kurniawan Nasution (Universitas Harapan Medan, 2019)
Bomb calorimeter is related to the measurement of the amount of energy of a material. Energy quantities include thermodynamic properties of systems such as enthalpy, internal energy, specific heat or heating value. Designing tools, data acquisition atmega 328p Performing acquisition data testing on bomb calorimeters, Confirming test data on sugarcane bio-ethanol fuel and pertalite sensors used are max6675 with type K thermocouple readings, 5 volt sensor operating voltage with a temperature reading range of 0.25 degrees at speed of 1 millisecond, data from the sensor is transferred to the micro control with the arduino program, the reading received by the micro control is the voltage. This value is converted into numbers with the help of the C++ program and stored in the ms.excel database with PLX DAQ. In this test, the LHV value for pertalite fuel is higher than bio ethanol. A bomb calorimeter device was developed which consists of a micro controller that functions as a measurement tool. The results of the implementation of the micro controller device on the bomb calorimeter can be said to be effective for use in testing fuel ratios. This effectiveness is seen from the test results. In this test, the HNY value on pertalite is higher than the sugarcane bio-ethanol fuel.